Covid-19 and The Homeless: Implications for Social Welfare Practice and Education in Ghana - Agyemang, Eric; Deku, Charles, Selorm; Forkuor, John, Boulard (My University, 2020)
COVID-19 as a pandemic has had severe implications on every country including Ghana. Although it has affected all persons, it’s implication on the vulnerable, particularly the homeless is immeasurable. This reflexive writeup aims to highlight the interventions made by the Government of Ghana for the homeless amidst COVID-19 and recommend ways to improve these interventions. In this essay, although I indicated that temporal interventions such as food, housing units and money were made available for head porters, a category of the homeless. I argue that these interventions should be made available for all category of homeless and also, the Government of Ghana should adopt sustainable ways of making these interventions permanent, so as to improve the living conditions of the homeless.
Supplemental Materials: https://osf.io/aehqj/
Keywords: COVID-19; Homeless; Vulnerable groups; Social Work Education